Mobile Learning Based on Procedural and Conceptual Knowledge on Fractional for Elementary School - Anis Andriah; Mohammad Faizal Amir (Universitas Pendidikan Ganesha, 2021)
As the impact of the Covid-19 pandemic, distance learning requires teachers to make learning more interesting yet achieve learning outcomes. This study aims to produce a valid, practical, and effective product in mobile learning based on procedural and conceptual knowledge for elementary school students. This study uses Research and Development with the ADDIE model. The subjects of this study were 11 elementary school fifth-grade students. The material and media expert is a lecturer in mathematics education and information technology education, respectively. The validity test was carried out using the expert judgment method. Eleven fifth-grade elementary school students assessed the practicality and effectiveness tests to determine the responses and results in fractional mathematics after using the developed mobile learning. This study uses both quantitative and qualitative data, which were collected using questionnaires and learning outcomes tests. The validity of mobile learning produces an average of 3.59 or is in the interval 2.50 ≤ Rv ≤ 4.00 with valid criteria. The effectiveness of mobile learning is obtained from the pretest and posttest data. The practicality of mobile learning obtained an average of 3.82 or is in the interval 2.50 ≤ Rk ≤ 4.00 with practical criteria. The effectiveness of mobile learning shows a significance value of 0.0010 or < 0.0050, which means that there are differences in student learning outcomes before and after using mobile learning. Thus, the development of procedural and conceptual-based mobile learning on fractional material in fifth-grade elementary school can be categorized as valid, practical, and effective.